Zonas de ações comunicacionais em arte e tecnologia - ZACAT - Santos, Camila dos (2021)
This research on sound and visual poetics consists of an investigation on artistic communicational practices of an activist character. First, with experiments in 2019, through diversified strategies and proposals for different interlocutors, in different spaces in the city of Santa Maria, Rio Grande do Sul – streets, museums, art galleries, university, school, social networks, radio wave space. Subsequently, as a result of the world scenario presented from 2020, with the SARS-CoV-2 virus pandemic, which causes the New Coronavirus disease, the COVID-19, the poetic undergoes significant transformations. In addition to the artistic and communicational strategies undergoing changes in approach, the space in Santa Maria moves to the Clube Naturista Colina do Sol (CNCS), located in the municipality of Taquara, also in Rio Grande do Sul – an naturist place not urbanized and immersed with the wild environment the least interfered by human action. To approach the construction of this research, studies on methodology by the researcher and artist Sandra Rey (1953) are used. As a theoretical foundation, reference is made to the idea of micropolitics, a concept that refers to philosophers Michel Foucault (1926-1984) and Gilles Deleuze (1925-1995) and to art critic Suely Rolnik (1948), especially with regard to bias of everyday life in the context of the research. Activist artistic practices, on the other hand, are based on the experiences of Brazilian collectives from the 1990’s to today, as seen from the perspective of historiography from the 1950’s onwards, with Italian autonomist philosophers such as Giorgio Agamben (1942) and Franco Berardi (1949). To support the notion of Art and Communication, authors such as Mario Costa (1936), Fred Forest (1933), Christine Mello and Giselle Beiguelman are based on. The concept of device, on the other hand, emerges from theoretical research and mediates artistic practices, having as reference Agamben, Foucault, Vilém Flusser (1920-1991) and Gilbert Simondon (1924-1989). In short, this master's research involves from performances, through installations, audio, video and face-to-face interactivity experiments or via virtual networks, in search of a visibility of everyday micropolitics, with their memories, affections, formalized impulses of life or ephemeral in moments of encounters.